2022
DOI: 10.2147/ijgm.s343046
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Dependent Ferroptosis-Related Signature is Closely Associated with the Prognosis and Tumor Immune Escape of Patients with Glioma

Abstract: Background:Ferroptosis is an autophagy-dependent form of cell death, sometimes called "ferritinophagy". Its related pathway has been proven to regulate the programmed death of glioma stem cells. Mining autophagy-dependent ferroptosis-related gene (AD-FRG) signature could facilitate the discovery of mechanisms and therapeutic targets showing drug resistance to chemotherapeutic drugs. Methods: We exhaustively searched HADB, MSigDB and FerrDb datasets and obtained 25 genes confirmed to exist in autophagy and ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…In terms of somatic mutation, we found that the frequency of the IDH1 mutation was greater in the low-risk group, in contrast to the higher mutation rates seen in both PTEN and EGFR in the high-risk group (Figures 6A, B), suggesting that the mutation frequencies in those genes may have different effects on ferroptosis. Previous studies have shown that IDH-mut glioma patients had a better prognosis than those with wild-type IDH, across all WHO grades (11,40), that EGFR amplification was correlated with poor prognosis (59), and that PTEN mutations could promote the infiltration of immunosuppressive tumor-associated 8A-C). Indeed, the high degree of DNA damage and poor repair capacity seen in glioma cells is a trademark feature of cancer and is a determining factor in the growth of tumor cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of somatic mutation, we found that the frequency of the IDH1 mutation was greater in the low-risk group, in contrast to the higher mutation rates seen in both PTEN and EGFR in the high-risk group (Figures 6A, B), suggesting that the mutation frequencies in those genes may have different effects on ferroptosis. Previous studies have shown that IDH-mut glioma patients had a better prognosis than those with wild-type IDH, across all WHO grades (11,40), that EGFR amplification was correlated with poor prognosis (59), and that PTEN mutations could promote the infiltration of immunosuppressive tumor-associated 8A-C). Indeed, the high degree of DNA damage and poor repair capacity seen in glioma cells is a trademark feature of cancer and is a determining factor in the growth of tumor cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Gene signatures have been constructed from the investigation of 60-80 candidate genes (9,38,39) identified by previous publications. When Zhou and Sun downloaded 173 and 303 FRGs, respectively, from the ferrDB database (40,41), the overall number of candidate genes was relatively small. The numbers and functional classification of FRGs in the ferrDB are constantly updated as new information becomes available, and new analyses of ferroptosis signatures for glioma have become more necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Beclin-1-mediated autophagy is reported positively related to better prognosis in uveal melanoma [ 36 ], while ATG7 involved in autophagy correlated with increased survival in malignant pleural mesothelioma [ 37 ]. Autophagy accompanied with immune escape is also related to many human diseases including cancers, such as glioma [ 38 ] and lung adenocarcinoma [ 39 ]. Moreover, the side effects of chemotherapy drugs for cancers always induced organ damage including AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al. confirmed that autophagy-dependent ferroptosis-related signature is closely associated with the prognosis and tumor immune escape of patients with glioma ( 72 ). Therefore, we recognize autophagy should be one of the hubs between ferroptosis and immunity in glioma.…”
Section: Overview Of Ferroptosis and Potential Singling Pathway In Gl...mentioning
confidence: 96%